The formation of polycyclic hydrocarbons during smoking process of cheese - Arzu Akpinar-Bayizit; Tulay Ozcan; Oya Irmak Sahin; Lutfiye Yilmaz-Ersan (Mljekarstvo)
The smoking process determines the characteristic flavour, odour, colour and texture of several cheese varieties. Some smoke compounds are known to have bacteriostatic and antioxidant effects, and may act as preservatives. Smoked cheese is appreciated by consumers due to its sensorial properties. However, with smoking process there is a risk of formation of toxic polycyclic aromatic hydrocarbons (PAHs). This review emphasises the occurrence of polycyclic hydrocarbons on smoked cheeses and their health impacts.